Synthesis and properties of side-chain liquid crystalline polymers grafted with chiral dimers containing cholesteryl groups. Issue 5 (8th April 2020) - Huang, Haozhou; Cong, Yuehua; Lin, Zirui; Zhang, Baoyan
ABSTRACT: Two series of novel side-chain liquid crystal (LC) polysiloxanes grafted with chiral liquid crystalline dimers containing cholesteryl mesogens were synthesised. The chemical structure and LC properties of comonomers and polymers were characterised by FTIR, 1 H-NMR, DSC, TGA, POM and XRD. M1 and M2 were chiral nematic (N*) dimers, and M3 was an achiral LC monomer displaying nematic mesophase in a narrow mesomorphic temperature range, while the copolymers exhibited N* mesophase whose mesomorphic temperature ranges were much wider than those of the comonomers. Moreover, the glass transition temperatures and isotropization temperatures of the polymers all decreased with decreasing the dimer components. Reflection spectra showed that Pa series tend to attain wide-band selective reflection at long wavelengths, while Pb series were more potential at short wavelengths with narrow bandwidths. Decreasing the dimer components led the wavelength of the selective reflection to blue shift, which was an abnormal phenomenon in chiral mixture system. Graphical abstract: